Trading psychology for dummies - Ullrich, Roland (For Dummies, 2022)
Keep your head in the game! Make smarter, confident trades in global markets Trading is 80% psychology and 20% methodology. Trading Psychology For Dummies helps you develop the mindset you need to respond correctly in any market condition. Make more money on your trades as you develop mental strength, act confidently, and avoid the typical mistakes traders make when they don't understand their own minds. This book is for traders with any portfolio size and any risk tolerance. With the clear and easy approach that has made Dummies investing books so wildly popular, you can take your trading skills to the next level. When you stop underestimating how much your psychology governs your returns, you'll discover ways to tweak your own thought process for better trading results. Learn how human psychology influences decision making in financial markets and other areas of life Discover advice and techniques that you can try right away to make more rational trades Examine how institutional investors account for market psychology when they predict price movements Earn better returns with the perspective of veteran traders who apply psychology-based techniques dailyTrading Psychology For Dummies gives an edge to novice and experienced traders alike. Gain confidence and maintain a flexible and open mind when trading.